Strategic communication skills in the higher education, Agricultural career - Paz, María Fernanda; Franco-Rodríguez, John E; Palacios-Rabasco, Zoila M. (Journal of business and entrepreneurial studie, 2020)
The article exposes the research conducted to the professors of the AGROPECUARIA Career of the Faculty of Technical Education for Development of the Universidad Católica de Santiago de Guayaquil. The objective of this research project is to review and identify teaching practices in relation to the communication strategy in the higher education classrooms. The information was collected based on semi-structured surveys of 32 students in Freshman year of college B 2018 and A 2019. The results have shown that the communication strategy of teachers has strong and weak points, which are relevant for the best class development. In conclusion, there are skills to improve as they are necessary for professional teaching performance.